PENGELOLAAN SANITASI DI KAWASAN PEDAGANG MAKANAN KAKI LIMA KOTA PAYAKUMBUH - Adha, Hari Nandio; Yuliana, Yuliana; Waryono, Waryono (Journal of Home Economics and Tourism, 2016)
This purpose of research is to describe sanitation management in street food payakumbuh are evaluated from:equipment, sanitary facilities.This type of research is descriptive qualitative with method of survey. Techniques of collecting data using interviews, observation, and documentation.The final conclusion is equipment: planning a choose equipment has already meeth the rules,organizinga wholeness equipment, lack of knowledge merchants about as a result of using defective equipment. Actuating washing equipment, their circuit process of washing equipment which are not done correctly. Controlling equipment storage, is not storage in the right place and contrary to the supposed. Evaluation not maximal, characterized by the persistence of the merchants that is not according to the rules.Planning sanitary facilities have been planned but not sufficient the need of merchant. Organizing not follow the rules. Actuating the work has not been done withmaksimum because still yheir steps do not work. Controlling is very less marked with a damaged facility. Evaluatinga lack of awareness of traders to remove trash and leave the premises selling locations without cleaning it first. Keyword: Sanitation Management, Street foodPayakumbuh